Study on adoption and impact of potato variety UNICA in Peru - International Potato Center; Laterite (2024)
This document outlines the proposed design for an adoption and impact study of potato variety UNICA, developed by the International Potato Center (CIP) and launched in Peru in 1998. UNICA stands out as a remarkable agricultural innovation due to its high productivity, resistance to diseases, and adaptability to diverse climates. Originally bred from the Lowland Tropics Virus Resistance (LTVR) breeding population, it was designed to enhance food security and improve farmers' incomes globally. Its ability to thrive in both mountainous and lowland environments, coupled with resistance to potato viruses and late blight—a devastating disease—has contributed to its widespread success. The design aims at answering the following research questions: What are the effects of adopting UNICA on farmers’ income, livelihoods, and employment? What factors promote the adoption of the UNICA variety, and what elements contribute to ensuring its long-term sustainability?